Sociopragmatics Analysis of The Joker’s Madness Through Face Theory - Imam Hanafi; Andri Wardana; Nola Nur Fadillah; Yasmiin Butsainah Rihhadatul Rahman (Universitas Islam Lamongan, 2025)
This study examines the role of sustained face-threatening acts (FTAs) in the psychological decline of Arthur Fleck in Joker (2019) and their contribution to identity fragmentation. This study aims to explain how recurrent threats to positive and negative face function as a sociopragmatic mechanism that erodes self-esteem and accelerates psychological disintegration. Drawing on Brown and Levinson’s (1987) face theory, the study adopts a qualitative descriptive approach to identify and classify FTAs across six key scenes and interpret them within their broader social contexts. The analysis reveals that Arthur is persistently subjected to bald-on-record and unmitigated FTAs that undermine his positive face, while his negative face is constrained in institutional interactions, particularly in therapeutic settings. These patterns reflect clear power asymmetries and demonstrate how linguistic marginalization aligns with broader forms of social exclusion. The study concludes that the cumulative impact of FTAs constitutes a sociopragmatic process through which micro-level linguistic aggression contributes to the erosion of identity and the narrative transformation of Arthur Fleck into the Joker.